2019
DOI: 10.15174/au.2019.2041
|View full text |Cite
|
Sign up to set email alerts
|

Metodología para analizar las variables que impactan en la viabilidad de un proyecto para generar energía a partir de un SDF. Estudio de caso: Pachuca, Hidalgo

Abstract: Se presenta una metodología que integra variables internas y externas, en tres estadios, que determinan la viabilidad de un proyecto de generación de energía elécrica, a partir del biogás captado del sitio de disposición final (SDF) del municipio de Pachuca, Hidalgo. Primero, se analiza el SDF a nivel técnico-financiero, con una proyección de 20 años, con y sin certificados de carbono, resultando viable el proyecto. El segundo estadio (regional) determina que las variables que más impactan son los tiempos de g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Less progress was observed in the development of national and municipal guidelines for HMS implementation. A study that analyzed the implementation and sustainability of a health strategy found that having clear and consistent guidelines are a strength for its implementation ( 22 ). However, if the regulatory framework does not respond to the context, implementation is a greater challenge, making it necessary to prepare regulations jointly with representatives of civil society and other stakeholders ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less progress was observed in the development of national and municipal guidelines for HMS implementation. A study that analyzed the implementation and sustainability of a health strategy found that having clear and consistent guidelines are a strength for its implementation ( 22 ). However, if the regulatory framework does not respond to the context, implementation is a greater challenge, making it necessary to prepare regulations jointly with representatives of civil society and other stakeholders ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is likewise recognized that municipal plans having an impact on the social determinants of health are strengthened by social participation ( 29 ), favoring the continuity of actions ( 30 ). On the contrary, limited social participation limits people’s acceptance of the HMS ( 22 ).…”
Section: Discussionmentioning
confidence: 99%